Fe/Fe3C Nanoparticles Embedded in Nitrogen‐Doped Carbon Nanotubes as Multifunctional Electrocatalysts for Oxygen Catalysis and CO2 Reduction. Issue 3 (12th December 2017) - Jia, Jingchun; Yang, Huijuan; Wang, Genxiang; Huang, Peng; Cai, Pingwei; Wen, Zhenhai
Abstract: Hybrids of Fe/Fe3 C embedded in N‐doped carbon nanotubes (Fe/Fe3 C@NCNTs) are prepared by pyrolyzing mixtures of Fe3 O4 nanoparticles and dicyandiamide. The systematic electrochemical study of Fe/Fe3 C@NCNTs shows a decent catalytic activity toward the oxygen evolution reaction (OER) and the oxygen reduction reaction (ORR). The sample of Fe/Fe3 C@NCNTs at 750 °C exhibits a remarkably high activity with an onset potential of 1.47 V for the OER, and an onset potential of 0.96 V and half‐wave potential 0.88 V for the ORR, which inspired us to set up a rechargeable Zn‐air battery with such Fe/Fe3 C@NCNT nanohybrids as the cathode materials, showing a maximum power density of 198 mW cm −2 and long‐term stability after 500 cycles. We also demonstrate that Fe/Fe3 C@NCNTs present favorable electrocatalytic activity towards the CO2 reduction reaction (CO2 RR) with a low onset potential and good selectivity. The major products are a mixture of H2 and CO gases that can be used for methanol production in the Fischer−Tropsch process. Abstract : All‐round activity : Hybrids of Fe/Fe3 C embedded in N‐doped carbon nanotubes (Fe/Fe3 C@NCNTs) are prepared by pyrolyzing mixtures of Fe3 O4 nanoparticles and dicyandiamide. Fe/Fe3 C@NCNTs show a highly multifunctional catalytic activity for the oxygen evolution, oxygen reduction, and CO2 reduction reactions.